Effect of pruning intensities on national and trinity cocoa established with three propagative methods - Vera Chang, Jaime; Moreno Cano, Cinthia Johanna; Salazar Pacheco, Martha Betania (Revista Colombiana de Investigaciones Agroindustriales, 2021)
Three pruning intensities were evaluated in two varieties (National and Trinitary) of cacao (Theobroma cacao L.), established with three propagative methods, a completely random design was used within a bifactorial arrangement as the first pruning factor (no pruning, pruning moderate, drastic pruning), as a second factor, cocoa propagation (seed, twig and graft) was evaluated as a response variable: (number of healthy pods (NMS), fresh weight, total pods. Yield kg/ha-1/year) sanitary variables (number of witch’s brooms (NEB), number of diseased pods (NME), physical quality indexes of cocoa (seed index, length and width of the almond). As main results it was obtained that the T9 moderate pruning, IMC-67-Graft CCN-51) followed by T21 (Drastic pruning, Seed CCN-51), reporting the highest number of healthy ears, the highest number of total ears indicating and the best yields kg/ha-1/year, the T18 (Drastic pruning, twig CCN-51) obtained the lowest n number of sick ears and witch’s brooms followed. In almond physical quality, T5 (Without pruning, EET-103-EET-103 Graft) presented the highest value in the highest seed index, and in the length and width of the almond. Concluding that the type of pattern - Forastero graft with Trinitary is recommended moderate pruning, in National Pattern National Graft with National a better response can be obtained